2014
DOI: 10.1155/2014/878926
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Iodine Deficiency among Pregnant Women in Haramaya District, Eastern Ethiopia: A Community-Based Study

Abstract: Background. Iodine deficiency in pregnancy is a worldwide problem. This study aimed to assess prevalence and predictors of subclinical iodine deficiency among pregnant women in Haramaya district, eastern Ethiopia. Methods. A cross-sectional, community-based study was conducted on 435 pregnant women existing in ten randomly selected rural kebeles (kebele is the smallest administrative unit in Ethiopia). Data on the study subjects' background characteristics, dietary habits, and gynecological/obstetric histories… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
4
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 29 publications
5
15
4
3
Order By: Relevance
“…Cabbage contains thiocyanate and isothiocyanate that inhibit iodine uptake by the thyroid follicular cells and also blocks the thyroid peroxidase enzyme [16]. e present nding is supported by reports of the previous studies [11,17,18].…”
Section: Discussionsupporting
confidence: 86%
“…Cabbage contains thiocyanate and isothiocyanate that inhibit iodine uptake by the thyroid follicular cells and also blocks the thyroid peroxidase enzyme [16]. e present nding is supported by reports of the previous studies [11,17,18].…”
Section: Discussionsupporting
confidence: 86%
“…For example, in Oromia, the largest populated region, seven studies investigated iodine level in food and water, and ID prevalence in children and women (Table 2). Only few areas of Jimma zone [7,11,18], Arsi zone [19], Bale zone [20] and Haramaya district [21] were covered, while other zones and districts have no information. Southern Nation Nationalities and Peoples were targeted with three independent studies of zones and districts such as Gamo Gofa [19], Kafa [22], Sidama [23][24][25], Hawasa [26] and Sodo [27,28].…”
Section: Regional Studies Of Id In Ethiopia Are Incompletementioning
confidence: 99%
“…In the same year 88.9 % of pregnant women visiting Jimma University Specialized Hospital for antenatal care were iodine deficient with a median urinary iodine (MUI) of 48 μg/L [18]. A comparable study from 2014 found 82.8 % of pregnant women in the Haramaya district to be deficient with a MUI of 58.1 μg/L [21]. Similarly, a study from 2013 among non-pregnant women living in rural communities of Sidama zone, found that 96.5 % had UIC below 100 μg/L with a MUI of 37.2 μg/L [24].…”
Section: Id Prevalence In Ethiopian Womenmentioning
confidence: 99%
See 1 more Smart Citation
“…These include deficits in hearing and speech, impairments of learning and memory, mental retardation and psychomotor and motor dysfunction (Prieto et al, ; Charlton et al, ). In spite of these adverse consequences, recent studies have still demonstrated that iodine intake during gestation is low (Ghassabian et al, ; Kedir et al, ; Majumder et al, ). Recently, there is an increasing iodine nutrition assessments indicate that a substantial part of child‐bearing women is in a state of marginal ID (Ferreira et al, ; Méndez‐Villa et al, ; Zimmermann et al, ).…”
Section: Introductionmentioning
confidence: 99%